2022
DOI: 10.21776/ub.jepa.2022.006.01.17
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Marketing Mix 7P terhadap Kepuasan dan Loyalitas Konsumen Produk Olahan Kopi Espresso di Kota Semarang

Abstract: Bauran pemasaran sebagai salah satu strategi pemasaran digunakan untuk merumuskan rancangan strategi pemasaran yang taktis dan efektif. Penerapan bauran pemasaran atau marketing mix 7P yang terdiri dari product, price, place, promotion, people, process dan physical evidence perlu dilakukan untuk memperbaiki dan mempertahankan sasaran pasar serta dapat dijadikan bahan evaluasi dalam bersaing dengan kompetitor untuk meningkatkan penjualan produk dan berorientasi kepada kepuasan dan koyalitas konsumen. Penelitian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
3
0
2
Order By: Relevance
“…The physical evidence factor, according to research by (Dhita et al, 2022) states that the physical evidence variable partially has a significant positive effect and previous research by (Khotimah & Astuti, 2022) states that the physical evidence variable partially has a significant effect on satisfaction. It can be concluded that the higher the customer satisfaction with the physical evidence that supports the service, the higher the customer's confidence to return to using the services of the Tax and Management Consultant Dr. Sudarno, S.Pd., M.M., BKP and colleagues.…”
Section: Introductionmentioning
confidence: 99%
“…The physical evidence factor, according to research by (Dhita et al, 2022) states that the physical evidence variable partially has a significant positive effect and previous research by (Khotimah & Astuti, 2022) states that the physical evidence variable partially has a significant effect on satisfaction. It can be concluded that the higher the customer satisfaction with the physical evidence that supports the service, the higher the customer's confidence to return to using the services of the Tax and Management Consultant Dr. Sudarno, S.Pd., M.M., BKP and colleagues.…”
Section: Introductionmentioning
confidence: 99%
“…The results of research by Dhita et al, (2022) show that the variables product, price, place, people, process, and physical evidence have a positive effect, while the promotion variable has a negative effect on consumer satisfaction and loyalty. Consumer satisfaction has a direct positive effect on consumer satisfaction and loyalty.…”
Section: Previous Studies Similar Research Conducted Bymentioning
confidence: 99%
“…Kualitas produk dapat menarik perhatian konsumen untuk memilih produk dengan kualitas terbaik sesuai dengan keinginannya. Kualitas produk merupakan salah satu faktor yang mendorong terciptanya sikap loyalitas, sehingga produsen atau penjual harus meningkatkan kualitas guna mempertahankan loyalitas konsumen (Dhita, Mukson, & Setiadi, 2022). Kualitas suatu produk yang sudah dipercaya konsumen dapat meningkatkan loyalitas dan membuat konsumen bersedia menggunakan serta membeli ulang produk tersebut.…”
Section: Kualitas Produkunclassified